A Critical Review and Meta‐Analysis of the Associations Between Acculturation and Alcohol Use Outcomes Among Hispanic Americans. (12th August 2018) - Lui, P. Priscilla; Zamboanga, Byron L.
Abstract : Acculturation has been studied as one key sociocultural determinant that helps explain ethnic disparities in alcohol use outcomes among Hispanic Americans. Primary studies and other systematic reviews have found between‐study inconsistencies regarding the extent to which acculturation is associated with alcohol use outcomes among Hispanic Americans. To better examine whether acculturation is distinctly linked to drinker status, drinking frequency, volume, intensity, binge drinking, and hazardous alcohol use/drinking problems, and to identify individual and methodological factors that moderate these associations, we conducted a comprehensive research synthesis. A systematic review was conducted on research pertaining to the associations between acculturation and alcohol use among Hispanics. We included 88 independent study samples ( N  =   68, 282) coded from 68 manuscripts published in 1987 to 2017. Standard and robust variance estimation (RVE) meta‐analyses were conducted to calculate the correlations between acculturation and overall alcohol use. We also conducted a series of analyses to examine the weighted mean correlations between acculturation and 6 specific drinking outcomes. We found a statistically significant correlation between acculturation and overall alcohol use ( r  =   0.09, p  <   0.001). Acculturation was associated with drinker status ( r  =   0.10, p  <   0.001), drinking intensity ( r  =   0.09, p  =   0.001), binge drinking ( r  =   0.05, p  =   0.006), and hazardous alcohol use/drinking problems ( r  =   0.06, p  =   0.006), but not drinking frequency ( r  =   0.02, p  =   0.56) or volume ( r  =   0.01, p  =   0.73). Gender, acculturation dimension, acculturation domain, age group, and sampling settings were found to explain between‐study variability in some of these associations. Findings show small relations between acculturation and various alcohol use outcomes, but the effects are relatively more robust among Hispanic women, adults, and when studies measured U.S. cultural orientation, linguistic acculturation, and behavioral practices. Abstract : This critical review included a comprehensive meta‐analysis of 88 published study samples examining the link between acculturation and alcohol use outcomes among Hispanic Americans. Acculturating to the mainstream U.S. culture, but not the traditional Latino culture, is associated with greater possibility of drinker status, higher levels of drinking intensity, binge drinking, and alcohol‐related problems. These findings are more salient among women than men. Other methodological and individual factors also moderate the relations between acculturation and alcohol use outcomes.